Analysis of entropy generation during natural convection in discretely heated porous square and triangular enclosures. (19th May 2017) - Das, Debayan; Basak, Tanmay
ABSTRACT: The present work involves the entropy generation studies within the porous square and triangular (models 1 and 2) cavities subjected to various discrete heating strategies at side walls (cases 1–4: symmetric heater locations, case 5: asymmetric heater locations) during natural convection over the wide range of Darcy number, , for various fluids ( P r m  = 0.015 and 7.2) at . Galerkin finite-element method has been used to solve the governing equations. The symmetric and asymmetric distributions of heaters have similar effects at lower D a m . However, the symmetric distribution of heaters corresponds to lower entropy generation rates at higher D a m . The triangular (model 1 and model 2) cavities are found to be optimal over the entire range of D a m ( ) based on the higher heat transfer rate and optimal entropy generation rates.